The Bidirectional Relation Between Counterfactual Thinking and Closeness, Controllability, and Exceptionality - Xie, Yibo; Beck, Sarah R. (Frontiers in Psychology, 2022)
In four experiments, we explored the inferences people make when they learn that counterfactual thinking has occurred. Experiment 1 (N = 40) showed that knowing that a protagonist had engaged in counterfactual thinking (compared to no counterfactual thinking) resulted in participants inferring that the past event was closer in time to the protagonist, but there was no difference in inferring how close the past event was between knowing that a protagonist made many or a single counterfactual statement(s). Experiment 2 (N = 80) confirmed that participants were not affected by the number of counterfactual statements they read when inferring temporal closeness. Experiment 3 (N = 49) demonstrated that participants who learned that a protagonist had engaged in counterfactual thinking were more likely to infer that the protagonist experienced the controllable event. Experiment 4 (N = 120) indicated that participants who learned that a protagonist had engaged in counterfactual thinking were more likely to infer that the protagonist experienced the exceptional event. We concluded that the existence (but not the number) of counterfactual thoughts can lead people to infer that events were close, exceptional, and controllable, which suggests that the relations between closeness / controllability / exceptionality and counterfactual thinking are bidirectional. These results showed that as well as making inferences based on facts about the real world, people also make inferences about the real world based on hypothetical worlds.